L2 perception of English vowels: testing the validity of Kuhl’s prototypes - García Lecumberri, María Luisa; Cenoz Iragui, Jasone (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1997)
The present study investigates confusion patterns in the identification of English vowel sounds by native Spanish learners. The aim was to test the validity of Kuhl's Native Language Magnet (NLM) theory for Spanish learners with an intermediate level of competence in English. Following this theory, the English and Spanish vowel systems were compared in order to obtain a set of L2 confusion predictions that could be derived from the NLM model. It was hypothesized that the prototype model would fail to account for all the confusion patterns in our data since our subjects interlanguage phonological system was no longer a direct reflection of their Ll system. A test was conducted in which subjects were asked to identify RP vowels in monosyllabic words after receiving specific phonetic training. It was observed that few perceptual confusions could be explained according to the NLM model as interpreted for L2 acquisition. We propose that the NLM theory can only account for L2 data if revisions are made as to the nature of prototypes in the interlanguage. The NLM model should also take into account other factors that may shape prototypes such as vowel duration and universals principles.